Reasons behind the Drop out of Street Children from Non-formal Primary Education Program - Chaitee, Nazmun Nahar (International Journal for Educational and Vocational Studies)
The aim of this study is to find out the inner reasons of dropping out of street children from non-formal primary education program. With this study also we can have a figure of the lifestyle, needs and social conditions of street children. To have the findings of my study qualitative research method will be conducted. In accordance with the study objectives from the large areas only 1 authority member, 1 teacher, 5 admitted children and 5 dropped out children were selected as sample. I designed open-ended questionnaire and semi-structured interview to collect my data. The thematic analysis method was used for data analysis. I have a variation in findings because of using questionnaire for teacher and authority and interview for children. Moreover in commonly I can say the demographic conditions, lacking’s of parental care and guidance, lacking’s of Interest and awareness, lacking’s of facilities, lacking’s of economic support, effects of misguidances, lacking’s of proper relationship among program stuff with parents and children’s are major problems that disturbed the street children to continue their education. Considering the findings it can be recommended that increasing of education program or giving support with educational equipment is not enough to continue education in this marginal sector of society. It is more important to grow consciousness, make them understood the importance of education, giving them a link of better future through education and make a reliable environment between education program and parents-children. Keywords: Street Children, Non-formal Education Program, Drop out